Fitamia Powder Drink as a Functional Food to Increase Hemoglobin Levels in Anemic Adolescent Girls - Ade Ifah Latifah; Hidayat Wijayanegara; Meti Widya Lestari; Teni Nurlatifah; Yanti Herawati; Ma'mun Sutisna (Jurnal Kebidanan dan Kesehatan Tradisional, 2025)
Background: The low interest in consuming Fe tablets is one of the factors that causes the standard management of anemia in adolescent girls to still not be optimal. Fitamia is a powdered drink combining carrot and ginger which aims to attract teenagers' interest in consuming functional drinks which have the potential to increase hemoglobin levels. The aim of the research is to analyze the effectiveness of Fitamia powder drinks in improving anemia in adolescent girls. Methods: This research uses a quantitative approach in the form of a randomized experiment with a pretest and posttest with control group design. Sampling used a multistage sampling technique. Data analysis used paired t-test, independent t-test, N-Gain percent, and Mann-Whitney. Results: Fitamia powder drink increased hemoglobin levels on the 31st day (p-value < 0.001) and on the 45th day (p-value < 0.001). The acceptability of Fitamia powder drinks is higher than Fe tablets in terms of color (p-value 0.007), aroma (p-value 0.011), taste (p-value <0.001) and lower gastrointestinal effects compared to Fe tablets (p-value < 0.001). Conclusion: Fitamia powder drink can increase hemoglobin levels in young women. The acceptability of Fitamia powder drink products is higher than Fe tablets and causes lower gastrointestinal effects than Fe tablets. Fitamia powder drink is recommended as an alternative iron supplementation for young women due to its effectiveness in increasing hemoglobin levels, higher acceptability, and fewer gastrointestinal side effects.